Epidemiologic characteristics, clinical management and Public Health Implications of Coronavirus Disease 2019 (COVID-19) in Pregnancy: A Systematic Review and meta-analysis - Sathian, Brijesh; Banerjee, Indrajit; Mekkodathil, Ahammed A; van Teijlingen, Edwin; Pizarro, Ana Beatriz; Asim, Mohammad; Mancha, Maraeh Angela; Kabir, Russell; Simkhada, Padam; Nascimento, Israel Júnior Borges do; Al Hamad, Hanadi (Nepal Journal of Epidemiology, 2021)
Background: The novel coronavirus disease 2019 (COVID-19) outbreak, caused by the pathogenic severe acute respiratory syndrome-2 (SARS-CoV-2) virus, is exponentially spreading across the globe. Methods: The current systematic review was performed utilizing electronic databases i.e. PubMed, MEDLINE and EMBASE. We searched for the keywords "COVID-19 AND "pregnancy" between January 1st, 2020 until December 31, 2020. Results: Out of 4005 records which were identified, 36 original studies were included in this systematic review. Pooled prevalence of vertical transmission was 10%, 95% CI: 4-17%. Pooled prevalence of neonatal mortality was 7%, 95% CI: 0-21%. Conclusion: The contemporary evidence suggests that the incubation period of COVID-19 is 2-14 days, and this infection could be transmitted even from the infected asymptomatic individuals. It is found that the clinical presentation of pregnant women with COVID-19 infection is comparable with the infected non-pregnant females, and the frequent symptoms were fever, cough, myalgia, sore throat and malaise. There are some cases with severe maternal morbidity and perinatal deaths secondary to COVID-19 infection. Under these circumstances, the pregnant women should focus on maintaining personal hygiene, proper nutrition and extreme social distancing to reduce the risk of COVID-19. Therefore, a systematic data reporting for evidence base clinical assessment, management and pregnancy outcomes is essential for prevention of COVID-19 infection among pregnant women.